Development of the RISKRES: Screening for risk factors and resilience contributing towards suicidality in adolescents and young people - GAFFNEY, MEGAN (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2019)
Youth suicide is a societal issue which warrants attention. The purpose of this study was to develop a psychometrically sound method to measure both risk factors and resilience as potential predictors of suicidality for adolescents and young people. A mixed method sequential design was employed, beginning with an iterative process guided by grounded theory methodology. Eighteen practitioners currently working with 'at risk' adolescents and young people (N = 18, 16 women, 2 men) participated in 4 focus groups. Following an iterative process of data collection and analysis, three major categories were generated as a theory of psychological resilience to suicidality. Results from the qualitative analysis, alongside review of the literature and feedback from subject matter experts guided item construction for the initial version of the RISKRES, which was further refined through statistical methods. An 'at-risk' sample of adolescents and young adults (N = 146, Mage = 16.46 years, age range: 11 - 22 years, median: 16 years, SD = 2.41) completed the RISKRES along with standardised screening tools for depression and suicidal behaviour (PHQ-9; SBQ-R). Following item analysis, the RISKRES was shortened to 29 items. Findings include an initial psychometric evaluation of the tool. Seven factors were extracted: Depression/ desperation; Anxiety/ agitation/ overwhelm; Autonomy; Disconnection; Capable/ future orientation; Connection; Bouncing back. While more complex, this may be preferable to measuring depression alone. The RISKRES subscales show promise as very brief stand alone measures. Development of the RISKRES will benefit from further validation with larger, more diverse samples and also from longitudinal data collection.
APPROVED
Keywords: suicide prevention; youth mental health; suicide screening; resilience; risk and protective factors